Insight into enrichment of anammox bacteria by a polyurethane sponge carrier coupled with iron-carbon micro-electrolysis under no strict anaerobic condition. (March 2022) - Cheng, Benai; Du, Jiangkun; Bao, JianGuo; Tufail, Haseeb; Xu, Tiantian; Zhang, Yi; Mao, Qidi; Faheem, Muhammad
Graphical abstract: Highlights: ICME-PS carriers can rapid enrichment of anammox bacteria. Small-pore carriers improved biofilm stability, while medium-pore carriers achieved long-term stable and efficient biofilms. ICME was firstly used for DO consumption and then mainly for nitrogen cycle reactions. ICME application reduced energy barriers to improve sludge aggregation. Abstract: A novel composite carrier (ICME-PS) was formed by coupling polyurethane sponge carriers (PS) with different pore sizes (15, 25, 40 ppi) and iron-carbon micro-electrolysis (ICME), which was used for enrichment of anammox bacteria and stable operation under no strict anaerobic condition. An increase of 5.67%-38.55% in specific anammox activity (SAA), an significant enhancement of biofilm stability and an improvement of 14.61%-42.38% in Ca.Brocadia were observed in ICME-PS, compared to PS carriers. ICME played a dual role: 1) contributed to the formation of an anaerobic microenvironment; 2) used for nitrogen cycle reactions. Additionally, small-pore carriers with highest biofilm stability can be used in high shear environments, while medium-pore carriers achieved the highest SAA in stable environments. Extended Derjaguin-Landau-Verwey-Overbeek (XDLVO) analysis indicated that ICME application reduced the energy barrier and improved aggregation performance. This study designed a novel composite carrier to broaden the application of anammox under no strict anaerobic condition.